A rare case of Erdheim-chester disease reported from Nepal. (August 2022) - Chhetri, Sunit; Manandhar, Srista; Neupane, Durga; Subedi, Sushil Sharma; Chhetri, Sunny; Acharya, Astha; Chaudhary, Sushant; Khatiwada, Pradeep; Shrestha, Suraj
Abstract: Introduction: Erdheim-Chester Disease (ECD) is a rare non-Langerhans cell histiocytosis with a propensity to involve multiple organs. Case presentation: We report a case of a patient in mid-60s with occipital headache and ataxia. Following the radiological and immunohistochemical investigations and genomic studies, a diagnosis of ECD was made with two intracerebral lesions. Brain lesions were resected and the patient was discharged with the medication Vemurafenib. After 3 years of diagnosis and 13 years of initial presentation, patient passed away. Discussion: ECD frequently presents with Diabetes Insipidus as initial presentation, long bone osteosclerosis as the most common presentation, and has multi-system predisposition. ECD can be differentiated from Langerhans Cell Histiocytosis (LCH) with immunohistochemistry images of the biopsy specimens. Further, with genomic analysis of ECD, the neoplastic nature has been highlighted and targeted therapies like Vemurafenib and Cobimetinib are shown to be effective. Conclusion: Good clinical judgement and supporting investigations can aid in diagnosing rare entities like ECD even in resource-limited settings. Highlights: Rare case of Erdheim-Chester disease with multi-system involvement presenting with initial features 10 years prior to diagnosis. Initially Diabetes Insipidus, followed by long bone and other multi-system involvement important cues for the diagnosis. Biopsy of the lesion and immunohistochemical analysis can help confirm the diagnosis. Genomic studies with mutational analysis further highlights the neoplastic nature of the disease. Advancement of genomic studies with targeted therapies like Vemurafenib and Cobimetinib key in of management of ECD.